- #1

binbagsss

- 1,277

- 11

**E**=(Ex,Ey,Ez)exp[itex]^{(i(k_{x}x+k_{y}y+k_{z}z-wt)}[/itex] and

**B**=(Bx,By,Bz)exp[itex]^{(i(k_{x}x+k_{y}y+k_{z}z-wt)}[/itex] ,

*where*

**k**= (kx,ky,kz),**to show that**

**k**X**E**=w**B**.So I'm mainly fine with the method. I can see the maxwell's equaion ∇X

**E**=-d

**B**/dt, is the equation required.

-d

**B**/dt=iw

**B**.

And using ∇X

**E**=i

**k**X

**E**, [1], the result follows.

My question is identifying equation [1]. How do you deduce this? Is it supposed to be obvious in any way. (

*I've done a check on the LHS and RHS so I can see its true*), but should this be obvious?

**Thanks in advance for your assistance .**